2016
DOI: 10.1002/2016gl068734
|View full text |Cite
|
Sign up to set email alerts
|

Stratospheric age of air variations between 1600 and 2100

Abstract: The current understanding of preindustrial stratospheric age of air (AoA), its variability, and the potential natural forcing imprint on AoA is very limited. Here we assess the influence of natural and anthropogenic forcings on AoA using ensemble simulations for the period 1600 to 2100 and sensitivity simulations for different forcings. The results show that from 1900 to 2100, CO2 and ozone‐depleting substances are the dominant drivers of AoA variability. With respect to natural forcings, volcanic eruptions ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 74 publications
(95 reference statements)
1
18
0
Order By: Relevance
“…The concentration of OH is increased throughout the atmosphere, apart from the lowermost levels. AOA will become notably younger within the stratosphere by the end of the century, as shown in various other studies (Austin et al, 2007(Austin et al, , 2013Butchart et al, 2006;Li et al, 2008;Muthers et al, 2016) and become slightly older (by a few days) in the troposphere. Vertical profiles of the CHBr 3 lifetime for present and future are shown in Fig.…”
Section: Quantification Of Future Atmospheric Changes Affecting Vsls mentioning
confidence: 65%
See 1 more Smart Citation
“…The concentration of OH is increased throughout the atmosphere, apart from the lowermost levels. AOA will become notably younger within the stratosphere by the end of the century, as shown in various other studies (Austin et al, 2007(Austin et al, , 2013Butchart et al, 2006;Li et al, 2008;Muthers et al, 2016) and become slightly older (by a few days) in the troposphere. Vertical profiles of the CHBr 3 lifetime for present and future are shown in Fig.…”
Section: Quantification Of Future Atmospheric Changes Affecting Vsls mentioning
confidence: 65%
“…Therein, VSLS emission fluxes are computed online from prescribed seawater concentrations. The simplified chemistry simulations use EMAC version 2.50 with sub- (Pozzer et al, 2006) (with the water-side transfer velocity parameterization k w = 0.222 u 2 + 0.333 u with respect to wind speed according to Nightingale et al, 2000), cloud, cloudopt, convect (with operational ECMWF convection scheme), cvtrans, ddep (Kerkweg et al, 2006a), ptrac (Jöckel et al, 2008), rad, scav (Tost et al, 2006), surface, and tnudge (Kerkweg et al, 2006b). The setup is as in Lennartz et al (2015); Hossaini et al (2016).…”
Section: Model and Experimentsmentioning
confidence: 99%
“…While some modelling studies reported a decreasing mean age of air following volcanic eruptions throughout the stratosphere (Garcia et al, 2011;Garfinkel et al, 2017), others show an increase in mean age (Diallo et al, 2017). Moreover, Muthers et al (2016) found a decreasing mean age of air in the middle and upper stratosphere and an increasing mean age below, while Pitari et al (2016a) found a decreasing mean age at higher levels of 30 hPa in the tropics and 10 hPa in the middle latitudes after the Pinatubo eruption. The HErSEA experiment in combination with a passive volcanic tracer might therefore help to better constrain the response of the BDC to volcanic eruptions using observations and help to clarify the uncertainties in the age-of-air changes after the Pinatubo eruption.…”
Section: Motivationmentioning
confidence: 98%
“…Through changes in the radiative properties of the stratospheric aerosol layer, volcanic eruptions are a significant driver of climate variability (e.g. Myhre et al, 2013;Zanchettin et al, 2016). Major volcanic eruptions inject vast amounts of SO 2 into the stratosphere, which is converted into sulfuric acid aerosol with an e-folding time of about a month, which might be prolonged due to OH depletion within the dense SO 2 cloud in the first weeks following a large volcanic eruption .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation